Special issue of the European Journal of Tourism Research "Mega Events and Tourism Policies" - Nunkoo, R.; Ramkissoon, Haywantee (International University College, 2012)
Recent years have witnessed an increasing number of mega events being hosted by destination. The role of mega events in destination development and marketing is well recognized. Such events also help destinations and economies to become distinctive and can aid in the formation of destination images. At the same time, the negative impacts of events have meant that their contributions to the sustainable development of the host destinations have been challenged. Few large-scale events live up to their full potential and deliver their long term promises. Further research is needed to ensure that the long-term benefits of mega events are maximized, their negative impacts are mitigated and their full marketing potentials are reached. With this as background, the purpose of this special issue is to provide event and tourism researchers, scholars, and policy-makers with a point of reference for research on mega events and their implications for tourism policies and planning. The volume consists of four peer-reviewed research papers on this topic.